Hubungan Antara Flexible Working Arrangement Terhadap Beban Kerja Subjektif Pada Dosen Universitas X - Safratul Ghina Dilla Afifa; Irin Riamanda; Risana Rachmatan; Santi Julita (Syiah Kuala Psychology Journal, 2025)
Lecturers are educators who have the main responsibility for disseminating knowledge through educational activities, research and community service. Lecture workload is defined as the average frequency of activities carried out within a certain period, in accordance with academic and professional responsibilities. Flexible Working Arrangement (FWA) was introduced as a flexible work scheme that allows adjustments to work time and location in a structured and sustainable manner. This research aims to determine the relationship between flexible working arrangements and subjective workload on lecturers at X University. This research uses a quantitative approach with a correlation type. The sampling technique uses quota sampling with a total sample size of 286 lecturers. The research data collectors involved lecturers who had a minimum position of Assistant Expert, did not hold a structural position, and were not on study assignments. The results of the research analysis showed that there was a negative relationship between flexible working arrangements and subjective workload for lecturers at X University, with a significant value (p)=0.006 and correlation coefficient value (r)=-0.163. This can be interpreted that the higher the flexible working arrangement, the lower the subjective workload. The results of the study also showed that the implementation of flexible working arrangements provides flexibility for workers to arrange work schedules according to personal preferences, thereby reducing the perception of workload. These results indicate that universities, including X University, can implement flexible working arrangements as a strategic policy to improve lecturer welfare, reduce perceived work pressure, and maintain productivity that the relationship between the flexible working arrangement variable is low on subjective workload in lecturers at X University.Dosen merupakan tenaga pendidik yang memiliki tanggung jawab utama dalam penyebarluasan ilmu pengetahuan melalui kegiatan pendidikan, penelitian, dan pengabdian kepada masyarakat. Beban kerja dosen didefinisikan sebagai frekuensi rata-rata aktivitas yang dijalankan dalam kurun waktu tertentu, sesuai dengan tanggung jawab akademik dan profesional. Flexible working arrangement diperkenalkan sebagai salah satu skema kerja fleksibel yang memungkinkan penyesuaian waktu dan lokasi kerja secara terstruktur dan berkelanjutan. Penelitian ini bertujuan untuk mengetahui hubungan flexible working arrangement dengan beban kerja subjektif pada dosen Universitas X. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis korelasi. Teknik penentuan sampel menggunakan quota sampling dengan jumlah sampel sebanyak 286 dosen. Pengumpulan data penelitian melibatkan dosen yang memiliki jabatan minimal asisten ahli tidak menduduki jabatan struktural, dan tidak sedang tugas belajar. Hasil analisis penelitian menunjukkan bahwa terdapat hubungan yang negative antara flexible working arrangement dengan beban kerja subjektif pada dosen Universitas X, dengan nilai signifikansi (p)=0,006 dan nilai koefisien korelasi (r)=-0,163. Hal ini dapat diartikan bahwa semakin tinggi flexible working arrangement maka semakin rendah beban kerja subjektif. Hasil penelitian juga menunjukkan bahwa penerapan flexible working arrangement memberikan keleluasaan bagi pekerja untuk mengatur jadwal kerja sesuai preferensi pribadi, sehingga mengurangi persepsi beban kerja. Hasil ini mengindikasikan bahwa perguruan tinggi, termasuk Universitas X, dapat menerapkan flexible working arrangement sebagai kebijakan strategis untuk meningkatkan kesejahteraan dosen, mengurangi tekanan kerja yang dirasakan, dan tetap menjaga produktivitas bahwa hubungan variabel flexible working arrangement rendah terhadap beban kerja subjektif pada dosen Universitas X.